WAYS TO DEVELOP STUDENTS' CREATIVE THINKING SKILLS BASED ON AN INTEGRATIVE APPROACH (European Journal of Pedagogical Initiatives and Educational Practices, 2026)
This article comprehensively analyzes the theoretical and practical aspects of developing students' creative thinking skills based on an integrative approach. The study substantiates the didactic potential of interdisciplinary integration, problem-based learning technologies, project-based learning, and digital learning tools in the formation and development of students' creative potential. It also reveals mechanisms for developing independent, critical, and creative thinking competencies in students through the effective integration of modern pedagogical technologies into the educational process. The results of the study show that an integrative approach is an important factor in increasing the effectiveness of education.